1980
DOI: 10.1017/s0007485300007902
|View full text |Cite
|
Sign up to set email alerts
|

The phenology of Oscinella spp. (Diptera: Chloropidae)

Abstract: Counts were made of the numbers of Oscinella adults caught in water traps in plots of grass and oats and in a suction trap in north-eastern England in 1969 and 1970. The numbers of eggs laid by O. frit (L.), O. vastator (Curt.), O. nitidissima (Mg.), O. hortensis Collin and O. maura (Fall.) on their respective host-plants were also counted. In both years, there were two generations of O. nitidissima and O. nigerrima (Macq.) and one of O. maura. In 1969, there were two generations of O. frit and one of O. horte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These results are similar to those of Oschmann (1982) who found up to 59.7% of the population of O.frit in a maize crop within 50 m of the edge of a large field. The results also support the view of Vickerman (1980) that all Oscinella spp. are not as migratory as O.frit.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These results are similar to those of Oschmann (1982) who found up to 59.7% of the population of O.frit in a maize crop within 50 m of the edge of a large field. The results also support the view of Vickerman (1980) that all Oscinella spp. are not as migratory as O.frit.…”
Section: Resultssupporting
confidence: 88%
“…Consequently adult O. frit migrates extensively and may differ from other species of the stem-borer complex. Vickerman (1980), for example, considered that O. vastator migrated less than O.frit. Mowat (1973Mowat ( , 1974, working with a different species complex, found that in addition to long distance migration, local migration was important, since emergence and populations were related to the location of previous crops.…”
Section: Introductionmentioning
confidence: 99%
“…Heathcote (1957) found that, for aphids, water traps may make catches when a population is scarce and when a sticky trap of reasonable size would not. In addition, Vickerman (1980) found that water traps in grassland always detected chloropid flies before suction traps.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed monitoring of the stem-boring larvae over six years at the Universi farm in both reseeded grassland (Italian ryegrass) and mixed swards of permanent pasture (where Xnsities are always very low), have always shown a very hi h incidence of 0. frit (consistently more than 90 YO), with much smaller numbers of 0. vastator a n t Geomyza trzpunctatu. Since graphs of the seasonal abundance of adult 'frit flies' at the farm were entirely consistent with those described specifically for 0. frzt in northern England by VICKERMAN (1980), it was clear that 0. frit was the overwhelmingly abundant species at the trap site and that for the purposes of this study speciation within the genus Oscinella was not necessary.…”
Section: Identificationmentioning
confidence: 99%
“…In the north, frit fly emerges in late May or early June and completes two generations (e.g. IBBOTSON 1961 ;VICKERMAN 1980). A knowledge of the relationships between the size and time of emergence of generations in one year in relation to those of the previous years, may be important in forecasting the size and time of emergence of future generations and hence, the likelihood of damage from this grassland pest.…”
Section: Introductionmentioning
confidence: 99%